2022
DOI: 10.3389/fpubh.2022.1058383
|View full text |Cite
|
Sign up to set email alerts
|

A perspective of massive open online courses (MOOCs) and public health

Abstract: Massive open online courses (MOOCs) have emerged as an innovative educational technology relevant to and affecting higher education, professional development, and lifelong learning. This paper introduces the principles of MOOCs and reviews the development of these platforms over time. We reflect upon the considerable investment by institutions to develop, deliver and promote such courses, particularly in public health. While open to interpretation, the inherent power, influence, and effectiveness of MOOCs is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…It seems reasonable that the use of MOOCs can improve health education. In fact, digital health literacy is already referred to as a superdeterminant of health [ 34 ]. Several studies have demonstrated the benefits of using MOOCs as promoters of learning about clinical aspects, serving as a tool that contributes to empowering individuals in making decisions about health issues [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable that the use of MOOCs can improve health education. In fact, digital health literacy is already referred to as a superdeterminant of health [ 34 ]. Several studies have demonstrated the benefits of using MOOCs as promoters of learning about clinical aspects, serving as a tool that contributes to empowering individuals in making decisions about health issues [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…I MOOCs can be accessed by anyone with an internet connection, and they often attract a large number of students from around the world. One of the key benefits of MOOCs is the flexibility, allowing students to learn at their own pace and on their schedule [5]. MOOCs also provide opportunities for individuals to learn new skills or explore new areas of interest without committing to a full degree program.…”
Section: Massive Open Online Course (Mooc)mentioning
confidence: 99%
“…Expanding the widespread utilization of Learning Management Systems (LMS) can be achieved by adopting Massive Open Online Courses (MOOCs). MOOCs adhere to the principle of openness and leverage advanced technology to facilitate the engagement of extensive participant numbers, making them accessible to the public (Badali et al, 2022;Bettiol et al, 2022;Ebben & Murphy, 2014).…”
Section: Introductionmentioning
confidence: 99%